Pemberdayaan Ibu Rumah Tangga dalam Meningkatkan Ekonomi Keluarga dengan Beriwirausaha Secara Mandiri di Desa Ngampelrejo, Kecamatan Jombang - Ulum, M Bustanul; Sa’diyah, Halimatus (Universitas Al-Falah As-Sunniyah Kencong Jember, 2023)
Good community empowerment activities generally require a mentoring process. This is important because the object of community empowerment is society with its various dynamics. So from this there are many abilities and skills of the community that must be developed. This mentoring activity was carried out in Krajan II Hamlet, Ngampelrejo Village, Jombang District, Jember Regency. This empowerment is specifically for housewives with a Pra Sejahtera family background. This activity is carried out by motivating housewives to do self-employment in their homes. So that later this home industry can develop in Ngampelrejo Village. One of the efforts to improve the community's economy in Krajan II Hamlet, Ngampelrejo Village is to create a new business, namely making cakes, which ingredients from the cake are easily found everywhere. The purpose of this empowerment is to improve the economy of housewives in the village so that they have an entrepreneurial mindset so that they can generate profits and benefits for their families. The result of this activity is an increase in the income of housewives. The conclusion is that with the housewife empowerment program in doing business independently, the income of housewives can increase.